Perlindungan Hukum Terhadap Pekerja Outsourcing Berdasarkan Undang-Undang Nomor 6 Tahun 2023 Tentang Cipta Kerja - Siagian, Ramot Andrew Christian; Zubaedah, Rahmi (Jurnal Ilmiah Wahana Pendidikan, 2025)
Outsourcing is a type of workforce that does not have a direct relationship with the company, where the workforce is transferred to another party or company. Outsourcing is the use of labor services recruited from third parties to fill certain positions in a company. Outsourcing arrangements are regulated in Article 64 of Law Number 13 of 2003 concerning Employment. Currently, legal protection for workers, including agency workers, is regulated in Law no. 6 of 2023 concerning Job Creation. The purpose of this writing is to understand the legal protection provided to outsourced workers in accordance with the provisions of applicable law. The type used in this research is a normative juridical approach method with an approach method using library material data (secondary data) such as an approach to statutory regulations.